New Tastes in Industrialized Countries and Transformations in the Latin-American Countryside:An Introduction to the Local Cases of Mexico and Chile - Arce, Alberto (The International Journal of Sociology of Agriculture and Food, 2021)
The recent reemergence of agriculture as one of the most dynamic setors of the Latin American econony has once again stimulated research interest in the rural sector. Of particular contemporary interest are the social and political effects of the new export agricultre at the local level. This paper explores the relationship between the social demand for fresh fruits and vegetables from the North and the variable responses of actors and localities engaged in the production of food. lt takes the production of new agricultural exports in Mexico and Chile as examples of the ways in which commodity circulation is re-organizing everyday practices while assessing some of the social consequences. The new rounds of interconnectivity beteen the South and North present opportunities to develop a more comprehensive analysis which includes spatial,cultural and social variability as one of the characteristics of the globalization tendency in agriculture. In conclusion, the paper presents some cultural, social and political issues surrounding the process of fruit and vegetable globalization and the significance of studying social discontinuities in rural sociology. Resumen Las Nuevas Preferencias en los Países Industrializados y la Transformación en el Área Rural Latinoamericana: Una Introducción a los Casos Particulares de México y Chile El reciente resurgimiento de la agricultura como uno de los sectores más dinámicos de la economía latinoamericana ha vuelto a estimular el interés por la investigación en el área rural. Los efectos sociales y politicos de la nueva agricu1tura de exportación a nivel local son en la actualidad de interés particular. Este trabajo examina la relación entre la demanda social desde el Norte de frutas y vegetales frescos y las diversus reacciones de los actores y las localidades involucradas en la producción de alimentos. A la vez, toma la producción de las nuevas exportaciones agricolas en México y Chile como ejemplo de las fonnas en que la circulación de mercancías está reorganizando las prácticas diarias, al mismo tiempo que evalúa algunas de las consecuencias sociales. Los nuevas giros de la interconexión entre eI Sur y el Norte representan buenas oportunidades para hacer un análisis más comprensivo, que incluya la variabilidad espacial, social y cultural de la tendencia a la globalización de la agricultura. En conclusión, este trabajo presenta algunos de los problemas sociales, politicos y culturaies que surgen alrededor del proceso de globalización de las frutas y vegetales frescos y la importancia de estudiar en la Sociologia Rural las discontinuidades sociales.